Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2012
DOI: 10.1145/2207676.2207751
|View full text |Cite
|
Sign up to set email alerts
|

On saliency, affect and focused attention

Abstract: We study how the visual catchiness (saliency) of relevant information impacts user engagement metrics such as focused attention and emotion (affect). Participants completed tasks in one of two conditions, where the task-relevant information either appeared salient or non-salient. Our analysis provides insights into relationships between saliency, focused attention, and affect. Participants reported more distraction in the non-salient condition, and non-salient information was slower to find than salient. Lacko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 24 publications
3
43
0
Order By: Relevance
“…The FA scale has been used in past work [28,30,31] to evaluate users' perceptions of time passing and their degree of awareness about what was taking place outside of their interaction with the task at hand. For our news reading task, participants were instructed to state on a 5-point Likert scale (strongly agree; disagree; neither agree nor disagree; agree; strongly agree) their agreement to each item shown in Table 3.…”
Section: Questionnairesmentioning
confidence: 99%
“…The FA scale has been used in past work [28,30,31] to evaluate users' perceptions of time passing and their degree of awareness about what was taking place outside of their interaction with the task at hand. For our news reading task, participants were instructed to state on a 5-point Likert scale (strongly agree; disagree; neither agree nor disagree; agree; strongly agree) their agreement to each item shown in Table 3.…”
Section: Questionnairesmentioning
confidence: 99%
“…Novelty and interest has also been explored with respect to online news and the user experience. Studies have shown that users will engage with content on topics extraneous to their primary interests with positive results (Toms, 2000), and will also be drawn ''off-task'' when they view salient content (McCay-Peet, Lalmas, & Navalpakkam, 2012). Thus, the familiarity of the news provider must be tempered with human tendencies to seek out content that is novel and/or interesting.…”
Section: Study 2: Ues and News Source Familiaritymentioning
confidence: 99%
“…Social search tools can be evaluated via two main criteria: effectiveness (and hence user satisfaction) and elicited engagement [15][16][17][18]. Often, shorter time to completion (i.e.…”
Section: Search Tool Evaluationmentioning
confidence: 99%
“…In a social setting, however, time to completion is not always a good metric: Social interactions can lead to increased engagement, which can in turn increase time to completion, such as through distortions in the subjective perception of time [15,19]. Since evaluations of social search tools depend on subjective measures, they are typically tested with user studies [15][16][17], which are limited in number of participants and constrained by the need for extended experience with a new tool [20]. Despite these problems, there is typically no viable alternative for testing users' subjective responses to search tools.…”
Section: Search Tool Evaluationmentioning
confidence: 99%